TOURISM VILLAGE DEVELOPMENT STRATEGY IN KOTAYASA VILLAGE, SUMBANG DISTRICT, BANYUMAS REGENCY THROUGH MACTOR ANALYSIS APPROACH - Supriadi, Dedi; Ramadhan, Dicky Satria; Suryahani, Irma; Kadarwati, Nunik (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p19, 2022)
The purpose of this study was to analyze the development strategy of the Kotayasa Tourism Village. The research was conducted by surveying 13 stakeholders from each agency and actor involved in it. The study used crosstab to determine the characteristics of respondents, followed by logistic regression to determine the demand for Kotayasa Tourism Village Objects, and used La Prospective Mactor analysis to analyze the relationship of actors to the development of Kotayasa Tourism Village. The results of this study indicate that the linkage of actors, actors who have an important role in the development of the Kotayasa Tourism Village include the Village Head, Pokdarwis, and Dinporabudpar, other actors become the carrying capacity in the development of the Kotayasa Tourism Village.